A Comparison of Financial Well-Being and Its Antecedents Across Different Employment Categories in Malaysia - Nurul Shahnaz Mahdzan; Mohd Edil Abd Sukor; Rozaimah Zainudin; Fauzi Zainir; Wan Marhaini Wan Ahmad (Gadjah Mada International Journal of Business, 2023)
This study compares the level of financial well-being (FWB) and its antecedents (financial stress, financial behaviour, financial literacy, and the internal locus of control (LOC)) across individuals of different employment categories in Malaysia. Second, it investigates the relationship between those antecedents and FWB and compares the differences in the strength. Data were collected from 1,867 respondents from four employment groups using a questionnaire-based survey. Descriptive statistics and analysis of variance (ANOVA) were conducted to achieve the first research objective, and ordinary least squares (OLS) regression was used to achieve the second research objective. The results indicate that FWB and its antecedents of Malaysian employees vary considerably across employment categories. The FWB of the unemployed and private-sector workers is significantly lower than their government sector and self-employed counterparts. Financial stress, financial behavior, and an internal LOC are the most determinative of employees’ FWB, however, they have varying degrees of impact across different employment categories. The results relate to employers and policymakers in formulating strategies to promote higher FWB among Malaysian employees, based on their employment categories.